RELATIONS BETWEEN MOTOR ABILITIES AND JUMP - SHOT IN BASKETBALL - Boris Nikolić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
The sample of 100 basketball players aged between twelve and fourteen, was subjected to the testing of motor abilities and specific motor abilities. The system of anticipated variables consisted of eighteen tests. Results were statistically processed and presented in the relevant tables which were discussed in the text.